PENGEMBANGAN AGROWISATA BERBASIS MASYARAKAT DI KABUPATEN KARANGANYAR - Sri Marwanti (Universitas Sebelas Maret, 2015)
Karanganyar Regency is home to various agricultural resources that can be developed into tourist attractions. However, these resources have not been optimally developed to strengthen the economy. Farmers have contributed to the development of agricultural resources as tourist attractions, even though their participation is still limited to notification efforts, information gathering and discussions. This research aims to 1) find out the needs of the farmers concerning the development of agritourism, 2) explore the regency’s government policies and programs concerning the development of agricultural resources as tourist attractions, and 3) formulate a community-based agritourism development model. Research data were obtained from field observation, in-depth interview, Focus Group Discussion, and content analysis. Data were analyzed using interactive and thematic analysis. The results show that 1) support and facilitation from stakeholders are needed in order to develop agricultural resources as tourist attractions, 2) the regency’s government policies and programs are still limited, and 3) this research leads to the recommendation of Community Empowerment in Developing Agritourism (CEDA) as a model for community-based agritourism development.